Factores de riesgo para enfermedades cardiovasculares: programa de prevención de la Universidad de Antioquia (1997)
ABSTRACT: The purpose of this study was to determine the characteristics of the presentation of cardiovascular diseases among teachers, non-teachers, retirees, beneficiaries and students referred to the Primary and Secundary Prevention of Cardiovascular Diseases Clinic of the Universidad de Antioquia, in Medellín, Colombia. Frequencies of exposure to risk factors are presented and the prevalent addociation among risk factors and symptom compatible with the coronary disease are presented. A high association between hypercholesterolemia and coronary disease was observed. Also, there was direct association with the number of risk factores and synergy among risk factor. Comparisons among risk factors are presented.